Promising results of stent graft placement for cephalic arch stenosis after repeated failure of angioplasty in patients on hemodialysis. Issue 6 (June 2020) - Feng, Pin-Chao; Lee, Chun-Hui; Hsieh, Hung-Chang; Ko, Po-Jen; Yu, Sheng-Yueh; Lin, Yu-Sheng
Objective: Cephalic arch stenosis (CAS) causes repeated dysfunction and failure of arteriovenous access. Percutaneous transluminal angioplasty is the standard initial treatment for CAS, but its outcome is unsatisfactory. This study aimed to evaluate the outcome of stent graft placement for CAS in patients on hemodialysis. Methods: A retrospective chart review from a tertiary medical center was performed in patients receiving stent graft placement for CAS between January 2012 and 2016. Patency was analyzed using the Kaplan–Meier method. Results: Twenty-one patients received stent graft placement for CAS. Technical and clinical success rates were 100%. Primary target lesion patency was 95% (95% confidence interval [CI], 86%–100%), 76% (95% CI, 58%–94%), and 43% (95% CI, 22%–64%) at 3, 6, and 12 months, respectively. No significant difference in patency was observed between the arteriovenous fistula and arteriovenous graft groups. Assisted primary patency was 95% (95% CI, 86%–100%), 71% (95% CI, 52%–91%), and 57% (95% CI, 36%–78%) at 3, 6, and 12 months, respectively. Secondary patency was 100% at 3, 6, and 12 months. Conclusions: After repeated failed angioplasty for cephalic arch stenosis, patients on hemodialysis who receive stent graft placement have effective and durable outcomes.